First and second apheresis in patients with multiple myeloma: no differences in tumor load and hematopoietic stem cell yield - Kiel, Katja; Cremer, Friedrich Walter; Ehrbrecht, Edith; Wallmeier, M.; Hegenbart, Ute; Goldschmidt, Hartmut; Moos, Marion (Bone marrow transplantation, 1998)
Autologous peripheral blood stem cells (PBSC) are now widely used to support myeloablative therapy in patients with multiple myeloma (MM). The presence of malignant cells in these autografts has been demonstrated. Characteristic kinetics with differential and concomitant mobilization of CD34+ and malignant cells after high-dose (HD) chemotherapy and hematopoietic growth factor administration have been reported. We determined the amounts of tumor cells and PBSC in leukapheresis products (LP) collected on day 1 (LP1) and 2 (LP2) from 16 MM patients harvested after HD chemotherapy and G-CSF. Furthermore, LP from six patients collected on day 5 (LP5) could be examined. The content of clonotypic cells was quantitated by an allele-specific oligonucleotide (ASO)-PCR assay based on limiting dilutions. CD34+ PBSC were determined by flow cytometry. The percentages of malignant cells in the leukapheresis products were in the range of 0% to 0.713% (mean 0.047%). CD34+ cells ranged between 0.06% and 5.4% (mean 1.23%). Comparing LP1 with LP2, no differences in the quantity of tumor cells (mean 0.0538% vs 0.0448%; P = 0.96) and CD34+ cells (mean 1.49% vs 1.33%; P = 0.50) were seen. The calculated number of tumor cells per CD34+ cell did not differ significantly (mean 0.0420 vs 0.0249; P = 0.65). Analyzing LP5 revealed no changes in the number of tumor cells per CD34+ cell (0.0511 vs 0.1044; P = 0.46) indicating a relatively constant ratio of PBSC to tumor cells during the course of PBSC harvesting. These results offer the possibility of combining LP harvested over several days without increasing the tumor load per CD34+ cell.